The scandal of secrecy - Lah, Peter (Gregorianum, 2020)
This article examines the notion of secrecy, specifically how it has been practicedin the governance of the Church. Hardly a new issue in this context, secrecy in recentdecades has been scrutinized as a possible cause of sexual abuse scandals, or at leastits enabling factor. After a brief presentation of sociological meaning of secrecy, theauthor presents three possible explanations of the phenomenon, namely administrativeefficiency and effectiveness, its psychological roots, and ecclesial and theologicalreasons for secrecy and transparency. Finally, a Christian argument in favor of transparency is presented, drawing upon Peter Henrici’s insistence on the primacy of truth in Christian communication.